The Influence of Nested Type of Integrated Science Learning Model on Students’ Critical Thinking and Cooperation Skills - Nurul Kamalia Habibah; Allesius Maryanto (Journal of Science Education Research, 2020)
The research aims to know the influence of the nested type of integrated science learning model on junior high school students’ (1) critical thinking skills, (2) collaboration skills, and (3) the critical thinking skills and collaboration skills simultaneously. This research is a quasi-experimental study with a nonequivalent control group design. The population of this research is the whole class VII of SMPN 2 Godean. The sampling technique was cluster random sampling, so that class VII A was obtained as an experimental class, and class VII C as a control class. The learning in experiment class was conducted by using a nested type science integration model with a scientific approach, while the learning in control class with the scientific approach that teachers normally use in learning. The instruments used in this research are (1) pretest and posttest critical thinking skills, (2) collaboration skills observation sheets, and (3) learning achievement sheets. The analysis technique used is the independent sample t-test, manova test, and effect size. The result showed that there was a significant effect of learning the integration of nested science types on junior high school students’ (1) critical thinking skills in the medium category, (2) collaboration skills in the medium category, and (3) critical thinking skills and collaboration skills simultaneously.